Effectiveness of An AI-Supported Psychological Program in Developing Emotional Regulation and Improving Offensive Performance Among Sitting Volleyball Players - Suhair Rahman Salman (Tadulako Journal Sport Sciences And Physical Education, 2026)
This study aimed to examine the effects of a structured educational program on specific volleyball skills and emotion regulation among students in an experimental group. The study employed a pre-test and post-test experimental design, in which participants completed skill assessments and emotion regulation scales before and after program implementation. The intervention was designed to provide a systematic learning experience through technical explanations, guided practice, repetitive performance tasks, feedback, and skill correction. Results The average score for tactical setting skills increased from 5.250 to 7.623, straight smash from position 3 increased from 2.750 to 5.583, crosscourt smash from position 3 increased from 3.500 to 7.250, straight smash from position 4 increased from 2.333 to 5.833, crosscourt smash from position 4 increased from 4.375 to 8.125, straight smash to the middle from position 2 increased from 2.416 to 6.916, and crosscourt smash to the middle from position 2 increased from 2.750 to 7.375. Emotion regulation also increased from 52.130 in the pre-test to 71.880 in the post-test. The calculated t-values ​​ranged from 6.524 to 29.850 for skill variables and reached 9.450 for emotional regulation, with all differences statistically significant at p < 0.001. Practically, this program can be used by teachers and coaches as a structured learning model to strengthen students' technical execution, tactical readiness, emotional control, and self-confidence during volleyball learning and training activities.